2021
DOI: 10.1186/s12884-021-03719-3
|View full text |Cite
|
Sign up to set email alerts
|

Labor dystocia and risk of histological chorioamnionitis and funisitis: a study from a single tertiary referral center

Abstract: Background Intrauterine inflammation affects short- and long-term neonatal outcomes. Histological chorioamnionitis and funisitis are acute inflammatory responses in the fetal membranes and umbilical cord, respectively. Although labor dystocia includes a potential risk of intrauterine inflammation, the risk of histological chorioamnionitis and funisitis of labor dystocia has not been evaluated yet. This study aimed to examine the association between labor dystocia and risk of histological chorio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Although amniotic fluid is not considered a sterile environment, the presence of intraamniotic sludge was associated with the risk of developing both clinical (RR: 2.95; 95%CI: 1.41-6.19) and histological chorioamnionitis (RR: 2.34; 95% CI: 1.7-3.12), which strengthens the hypothesis that sludge is a marker of microbial infection, which is the main known cause of premature labor. 37 These facts reiterate the hypothesis that sludge is an indicator of microbial invasion within the amniotic cavity, which would explain its relationship to clinical and histological chorioamnionitis, premature labor, and neonatal sepsis.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Although amniotic fluid is not considered a sterile environment, the presence of intraamniotic sludge was associated with the risk of developing both clinical (RR: 2.95; 95%CI: 1.41-6.19) and histological chorioamnionitis (RR: 2.34; 95% CI: 1.7-3.12), which strengthens the hypothesis that sludge is a marker of microbial infection, which is the main known cause of premature labor. 37 These facts reiterate the hypothesis that sludge is an indicator of microbial invasion within the amniotic cavity, which would explain its relationship to clinical and histological chorioamnionitis, premature labor, and neonatal sepsis.…”
Section: Discussionmentioning
confidence: 81%
“…Although amniotic fluid is not considered a sterile environment, the presence of intraamniotic sludge was associated with the risk of developing both clinical (RR: 2.95; 95%CI: 1.41–6.19) and histological chorioamnionitis (RR: 2.34; 95%CI: 1.7–3.12), which strengthens the hypothesis that sludge is a marker of microbial infection, which is the main known cause of premature labor. 37…”
Section: Discussionmentioning
confidence: 99%
“…We report a relatively high rate of histopathological chorioamnionitis after emergency CS. A previous study showed that labour dystocia increased the risk of histopathological chorioamnionitis 27 . The importance of histopathological chorioamnionitis should not be ignored, as it was found to be associated with EOS and perinatal comorbidities 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that labour dystocia increased the risk of histopathological chorioamnionitis. 27 The importance of histopathological chorioamnionitis should not be ignored, as it was found to be associated with EOS and perinatal comorbidities. 28 The reported rate of chorioamnionitis of 13% in women with positive uterine culture is higher than the rate of 1-4% reported in a large database.…”
Section: Maternal Intra\postpartum and Neonatal Outcomesmentioning
confidence: 99%
“…However, extended LD may cause recurrent, prolonged, and excessive reduction of uteroplacental perfusion, which may exceed the ability of the foetus to tolerate the hypoxia and lead to foetal asphyxia and acidosis. Furthermore, because labour is affected by inflammatory status in the myometrium, cervix, and foetal membranes 25 27 , prolonged LD may be associated with an inflammatory condition that may also affect foetal asphyxia and acidosis, along with the effects of labour dystocia on histological chorioamnionitis and funisitis 28 .…”
Section: Discussionmentioning
confidence: 99%